Eksplorasi Ragam Budaya dalam Pertukaran Mahasiswa Merdeka Guna Mempertebal Toleransi - Mei Sartika Pasaribu; Rhema Lisbet Manurung; Dosni Roham Damai Setia Farasi; Simon Panjaitan (Departement of Mathematics Education, 2023)
The social life and cultural diversity of the Indonesian nation is certainly the wealth of the Indonesian nation. The cultural system is the processes and results of systemic interactions from religious culture, scientific culture, defense culture, custom culture, and culture of togetherness, which are related to one another and are positively dynamic towards the advancement of national civilization. Through the Merdeka Student Exchange which is the Merdeka Campus Program which is attended by students from all universities in Indonesia from Sabang to Merauke, there is a meeting of cultural diversity brought by each student from various islands. With the aim of strengthening the sense of tolerance between the culture that is brought with the culture that is found in the destination tertiary institution. Tolerance is a very important attitude because it is an act that respects the diversity of backgrounds, views and beliefs. The method used is a holistic observation method (factual and literal) used as a data collection technique. As for the analysis technique using qualitative analytical methods. In this method the collected data is analyzed by inventorying facts with ideal concepts based on academic understanding and formal legal sources.